Effect of Bi contents on key physical properties of NiO NPs synthesized by flash combustion process and their cytotoxicity studies for biomedical applications. Issue 12 (15th August 2020) - Khan, Aslam; Shkir, Mohd; Ibrahim, Essam H.; Kilany, Mona; AlFaify, S.; Sayed, M.A.; El-Toni, Ahmed Mohamed; Aldalbahi, Ali; Rahaman, Hamidur; Siddiquei, Mohammad Mairaj
Abstract: Nickel oxide has tremendous applications in the field of biomedicine. In this study, NiO nanoparticles were synthesized with different Bi contents (NiO@Bi; 0.0–7.5 wt%), and multifunctional usages were investigated. Structural confirmation was conducted through XRD and Raman studies, which revealed a monophasic cubic system. With increasing Bi content, broadening of the XRD and Raman peaks were observed, indicating a reduction in particle size. The crystallite size was found to be in the range of 10–26 nm. The decrease in particle size was confirmed through dynamic light scattering measurement. The homogeneous distribution of all elements and the presence of Bi were detected by an EDX/SEM e-mapping study. Field emission electron microscopy confirmed the formation of spherical shape nanoparticles. The grain size was reduced from 30 nm to 10 nm with Bi content, in accordance with XRD and Raman results. The Kubelka-Munk method was employed to determine the effect of Bi content on the optical band gap of NiO. The energy gap was reduced with Bi content in the range of 3.32–3.50 eV. Antimicrobial and in vitro cytotoxic characteristics of the prepared NPs were also studied. The results revealed that all NiO@Bi NPs had negligible antimicrobial activity and no cytotoxic effects on both normal and activated splenic cells. The in vivo acute cytotoxicity study indicated no cytotoxic effects on liver and kidney functions. The prepared NiO@Bi NPs were implanted in living organisms without hepatic/renal toxicity, demonstrating excellent biocompatibility, cell viability, and superior quality of nanocrystals, suggesting that the prepared NPs are ideal candidates for antibacterial and biomedical applications. Graphical abstract: Image 1 Highlights: One step flash combustion route was used to achieve highly homogeneous NiO@Bi NPs facilely. XRD and FT-Raman spectroscopy approved the cubic NiO phase at all Bi contents. A systematic reduction in particle size was observed on increasing the Bi contents in NiO. Energy gap was reduced by Bi content and lie in 3.50 to 3.32 eV range. In-vivo acute cytotoxicity study indicates no cytotoxic effects on the kidney and liver.